Organizacje sieciowe, sieci strategiczne i łańcuchy dostaw - próba systematyzacji pojęć - Witkowski, Jarosław (Network Organizations, Strategic Networks and Supply Chain - an Attempt to Terminology Systematization, 2005)
The main aim of the paper is a comparative study concerning the origins, structure and purposes of network organizations and supply chains. Based on these analysis an integrated supply chains as well as a supply networks are classified to group of a strategic networks which in the new economic conditions are a good alternative for vertical integration and subcontracting. According to the author there are some key factors distinguished supply chains and networks from all strategic networks, such as: different genesis, dominant relations through all value chain and scope of activity mainly related to physical flows of goods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 180-189